Wolność religijna w social media: Ograniczenia i wyzwania dla twórców religijnych - Przybysz, Monika (Uniwersytet Kardynała Stefana Wyszyńskiego w Warszawie, 2022)
Social media platform owners are becoming more and more effective at controlling their users. And the users themselves are becoming more and more susceptible to manipulation. In an attempt to take a critical look at the issue of religious freedom in social media and at the model of oppressive management of these platforms, the idea of the panopticon should be recalled. For this purpose, among others, he used the concept of panopticon according to Jeremy Bentham. In this article, the research method will be a case study, which will allow for a broad analysis embedded in the critical stream of humanistic management, as well as the desk research method applied to analyze the phenomenon of removing or limiting the activity of Christian, religious and conservative accounts referring to Christian values. The subject of reflection will be the 3 biggest social media at present, that is Facebook, YouTube and Twitter as well as Google. The phenomena analyzed include: the use of censorship or the use of artificial intelligence to manipulate social network users, and above all, the clear limitation of Christians’ freedom to manifest Christian values in the social media space. Właściciele platform społecznościowych stają się coraz bardziej skuteczni w kontroli nad swoimi użytkownikami. Zaś sami użytkownicy stają się coraz bardziej podatni na manipulację. Próbując krytycznie spojrzeć na problematykę wolności religijnej w social media oraz na model opresyjnego już niestety zarządzania tymi platformami, należy przywołać ideę panoptykonu. W tym celu autor posłużył się między innymi koncepcją panoptykonu według Jeremy’ego Benthama. W niniejszym artykule metodą badawczą będzie studium przypadku, które pozwoli na szeroko zakrojoną analizę osadzoną w nurcie krytycznym zarządzania humanistycznego, a także metoda desk researchu zastosowana do analizy zjawiska usuwania lub ograniczania aktywności kont chrześcijańskich, religijnych i konserwatywnych odwołujących się do wartości chrześcijańskich. Przedmiotem refleksji staną się trzy ...